Pengembangan Media Pop Up Book Mata Pelajaran Bahasa Indonesia Dalam Meningkatkan Motivasi Belajar Siswa Kelas III di Mi Wahdatut Tholibin Bawangan Jombang - Nurafifah, Himmatul; Unsi, Baiq Tuhfatul (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2025)
This study aims to develop pop-up book learning media in Indonesian language subjects and to determine its effectiveness in increasing the learning motivation of grade III students at MI Wahdatut Tholibin Bawangan, Jombang. The background of this study is the low learning motivation of students in understanding Indonesian language materials which are less varied and interactive in their delivery.This study uses the Research and Development (R&D) method with the Borg and Gall development model which is simplified into several stages, namely, Analysis, Design, Development, Implementation, evaluation. The trial subjects were 21 students of class III MI Wahdatut Tholibin Bawangan.The validation results by media experts and material experts show that the developed pop-up book media is in the category of very feasible to use. The test results show a significant increase in student learning motivation after learning before and after using pop-up book media, which is indicated by the motivation questionnaire score, pretest and posttest to students.Thus, pop-up book media can be an alternative interesting and effective learning media to increase students' learning motivation in Indonesian language subjects, especially at the Madrasah Ibtidaiyah or Elementary School level.